Multigravida Preterm dengan IUGR pada Preeklampsia Berat: Sebuah Laporan Kasus - Febrina Halimatunisa nisa; Ratna Dewi Puspita Sari (Medula, 2022)
Intrauterine growth restriction (IUGR) is a baby born at term but has a low birth weight (LBW) due to impaired fetal growth while in the mother's womb. Intrauterine growth restriction (IUGR) is closely related to severe preeclampsia (PEB). In PEB there is interference with placental implantation, thereby reducing blood flow to the fetus. Reduced blood flow causes inadequate nutrition for fetal growth. Intrauterine growth restriction (IUGR) is a fairly common complication, where the prevalence reaches 3-7% of all pregnancies in developing countries. This study is a case report where Mrs. Ni, 41 years old with G3P2A0 34 weeks pregnant came to PONEK with clear discharge and heartburn up to the waist. On the os, it was found that the conjunctiva was anemic and the height of the uterine fundus did not match the gestational age. Laboratory examinations showed hemoglobin 10.4 g/dL, Hematocrit 32%, erythrocytes 3.7 million/ul, proteinuria ++. Based on the data above, the patient was diagnosed as Mrs. Ni, G3P2A0, 41 years old, 34 weeks gestation, single live fetus, intrauterine, breech presentation, right back, not yet inpartu with IUGR.